"The Jackson Table Is a Pain in the…": A Qualitative Study of Providers' Perception Toward a Spinal Surgery Table. Issue 1 (March 2018) - Asiedu, Gladys B.; Lowndes, Bethany R.; Huddleston, Paul M.; Hallbeck, Susan
Abstract : Objective: The aim of this study was to define health care providers' perceptions toward prone patient positioning for spine surgery using the Jackson Table, which has not been hitherto explored. Methods: We analyzed open-ended questionnaire data and interviews conducted with the spine surgical team regarding the current process of spinal positioning/repositioning using the Jackson Table. Participants were asked to provide an open-ended explanation as to whether they think the current process of spinal positioning/repositioning is safe for the staff or patients. Follow-up qualitative interviews were conducted with 11 of the participants to gain an in-depth understanding of the challenges and safety issues related to prone patient positioning. Results: Data analysis resulted in 6 main categories: general challenges with patient positioning, role-specific challenges, challenges with the Jackson Table and the "sandwich" mechanism, safety concerns for patients, safety concerns for the medical staff, and recommendations for best practices. Conclusions: This study is relevant to everyday practice for spinal surgical team members and advances our understanding of how surgical teams qualitatively view the current process of patient positioning for spinal surgery. Providers recommended best practices for using the Jackson Table, which can be achieved through standardized practice for transfer of patients, educational tools, and checklists for equipment before patient transfer and positioning. This research has identified several important practice opportunities for improving provider and patient safety in spine surgery.